2022
DOI: 10.31248/jeia2022.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality of electrical wires used for residential building wiring in Delta State, Nigeria

Abstract: The utilization of counterfeit and substandard building materials for residential building construction had become a major concern, due to the hazards the occupants of those buildings are being subjected to. This research was carried out to appraise the quality of electrical wires used for residential building wiring in Delta State, Nigeria, and to also investigate the reasons why property developers still use these substandard materials despite the glaring negative consequences. Three commonly used electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Materials with low resistivity indicate that they readily allow electric current to pass through them. Odoh et al, 2022;Obukoeroro and Uguru (2021b) reported that materials with high resistivity tend to build up high thermal energy within their bodies, when subjected to current flow. This heating up can lead to electrical fires, which is one of the major reasons why electrical fires are common in substandard electrical wires and cables.…”
Section: Electrical Resistivity Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials with low resistivity indicate that they readily allow electric current to pass through them. Odoh et al, 2022;Obukoeroro and Uguru (2021b) reported that materials with high resistivity tend to build up high thermal energy within their bodies, when subjected to current flow. This heating up can lead to electrical fires, which is one of the major reasons why electrical fires are common in substandard electrical wires and cables.…”
Section: Electrical Resistivity Of the Samplesmentioning
confidence: 99%
“…Additionally, Uguru and Obukoeroro (2020) and Odoh et al (2022) Choosing the appropriate materials is inevitable in composite production in order to achieve desired goals. The engineering properties of green conductive composites are influenced by crop varieties (Eboibi et al, 2019), pre-harvest treatment (Akpokodje and Uguru, 2019;, post-harvest treatment (Navdeep et al, 2012;Nyior et al, 2018), hybridization (Bao, 2008;Bratte and Uguru, 2021), and the maturation (Oghenerukewve and Uguru, 2018) of the reinforcing materials.…”
mentioning
confidence: 99%